ANCIENT REMEDIES FOR COUGHS AND COUGH-RELATED SYMPTOMS: ANALYSIS FROM MALAY MEDICAL MANUSCRIPTS - Raja Perdaus, Raja Nurhanin; Mohd Shafri, Mohd Affendi; Shahdan, Intan Azura (International Journal of Allied Health Sciences, 2021)
Cough, a common symptom with various underlying causes, may lead to debilitating consequences in terms of loss of employment, healthcare utilisation and psychosocial morbidity. This study aims to document information on coughs and cough-related symptoms from six Malay medical manuscripts. The information is related to terminologies, symptoms, list of materials, method of preparation, method of administration and dosage. The materials were then compared with contemporary studies on their relevant therapeutic action. It was found that batuk, lelah and esak are the most common terms related to coughs and cough-related problems in the Malay manuscripts. Coughs can then be categorised into five types: wet cough, dry cough, cold-induced cough, asthmatic cough and physiological coughs. Asthmatic cough has the greatest number of prescriptions (n=30) than other types of coughs. In total, 62 formulations have been documented involving about 93 plant species, 6 animals and 2 minerals. Fenugreek or Trigonella foenum-graecum is the common material prescribed for all five types of coughs. Honey, gandarukam and mustaki are also commonly prescribed for all coughs except dry cough. Future study may investigate the effectiveness of these traditional formulations and their therapeutic benefits to treat coughs and cough-related problems. With proper recommendation, practice and guidelines from health practitioners, health authorities should consider the availability of local materia medica in treating coughs as an advantage to improve the quality of life for the community at large. Keywords: Ancient manuscripts, kitab tib, Malay medicine, phytomedicine, respiratory distress